Conjugates of Phthalocyanines With Oligonucleotides as Reagents for Sensitized or Catalytic DNA Modification (Bioinorganic Chemistry and Applications)
Several conjugates of metallophthalocyanines with deoxyribooligonucleotides were synthesized to investigate sequence-specific modification of DNA by them. Oligonucleotide parts of these conjugates were responsible for the recognition of selected complementary sequences on the DNA target. Metallophthalocyanines were able to induce the DNA modification: phthalocyanines of Zn(II) and Al(III) were active as photosensitizers in the generation of singlet oxygen 1 O 2 , while phthalocyanine of Co(II) promoted DNA oxidation by molecular oxygen through the catalysis of formation of reactive oxygen species ( ⋅ O 2 − , O 2 H 2 , OH). Irradiation of the reaction mixture containing either Zn(II)- or Al(III)-tetracarboxyphthalocyanine conjugates of oligonucleotide pd(TCTTCCCA) with light of > 340 nm wavelength (Hg lamp or He/Ne laser) resulted in the modification of the 22-nucleotide target d(TGAATGGGAAGAGGGTCAGGTT). A conjugate of Co(II)-tetracarboxyphthalocyanine with the oligonucleotide was found to modify the DNA target in the presence of O 2 and 2-mercaptoethanol or in the presence of O 2 H 2 . Under both sensitized and catalyzed conditions, the nucleotides G 13 – G 15 were mainly modified, providing evidence that the reaction proceeded in the double-stranded oligonucleotide. These results suggest the possible use of phthalocyanine-oligonucleotide conjugates as novel artificial regulators of gene expression and therapeutic agents for treatment of cancer.